A silver-based tin oxide electrical contact material and preparation method thereof
By doping lithium and cerium into silver-based tin oxide electrical contact materials and preparing doped tin oxide fibers, combined with high-energy ball milling and vacuum discharge plasma sintering technology, the problems of poor processing performance and poor electrical performance of the material are solved, significantly improving the material's anti-welding and arc resistance and extending the electrical life.
Patent Information
- Application Number
- CN202510095717.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-22
AI Technical Summary
In actual production, existing silver-based tin oxide electrical contact materials have poor plastic processing performance, poor electrical performance, short electrical life cycle and contact resistance, and the interface bonding characteristics of tin oxide and silver matrix are poor.
Doped tin oxide powders are prepared by doping lithium and cerium at a high temperature solid phase method, and doped tin oxide fibers are made by electrospinning technology, and silver-based tin oxide electrical contact materials are prepared by combining silver powder high-energy ball milling and post-annealing of silver powder and vacuum discharge plasma sintering technology.
The interface bonding characteristics of tin oxide and silver matrix are significantly improved, the distribution of tin oxide particles in silver is improved, the material's anti-welding performance, arc corrosion resistance and electrical life are improved, and the contact resistance is reduced.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electric contact materials, in particular to a silver-based tin oxide electric contact material and a preparation method thereof. Background Art
[0002] In the electrical and electronic industries, electrical contact composite materials and components are key materials and components for instruments and electrical switches. They mainly connect and disconnect circuits and load currents. Their performance is a direct factor affecting the reliable operation and life of switchgear. Among them, silver-based cadmium oxide composite electrical contact materials are widely used due to their low contact resistance, resistance to welding, arc resistance, excellent plastic processing properties and weldability. However, silver-based cadmium oxide composite materials have serious environmental problems during service and will inevitably release cadmium vapor that affects human health.
[0003] Due to the urgent demand for health and environmental protection, people hope to develop a material that can replace silver-based cadmium oxide. For this reason, domestic and foreign developers have turned from silver-based cadmium oxide composite material systems to the research and development of environmentally friendly silver-based electrical contact composite materials. People have developed a series of silver-based metal oxide contact materials such as silver-based zinc oxide, silver-based tin oxide, and silver-based nickel oxide. However, studies have shown that silver-tin oxide materials have better resistance to fusion welding and arc erosion, and are the most promising non-toxic materials to replace silver-cadmium oxide.
[0004] As an alternative to the silver-based cadmium oxide composite material system, environmentally friendly silver-based tin oxide electrical contact composite materials have been successfully developed abroad and put into market application. However, although domestic developers have conducted a lot of experimental research on the research and development technology of silver-based tin oxide electrical contact composite materials, there are still poor and unstable plastic processing performance, poor electrical performance, short electrical life cycle, high contact resistance and other undesirable properties in the actual production process. Therefore, how to improve the interface bonding characteristics between tin oxide and silver matrix and improve the distribution of tin oxide particles in silver in the matrix has become the key to further improve the performance of silver-based tin oxide electrical contact materials. Summary of the invention
[0005] The object of the present invention is to provide a silver-based tin oxide electrical contact material and a preparation method thereof, so as to solve the problems existing in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A silver-based tin oxide electrical contact material comprises the following steps: firstly, lithium and cerium are doped by a high-temperature solid phase method to prepare doped tin oxide powder; tin chloride and copper nitrate are electrostatically spun into a fiber membrane while titanium dioxide is grown in situ, and then calcined to prepare doped tin oxide fiber; doped tin oxide powder, doped tin oxide fiber and silver powder are mixed by high-energy ball milling and then annealed to prepare silver-based tin oxide composite powder; and the silver-based tin oxide composite powder is pre-pressed and sintered to prepare the silver-based tin oxide electrical contact material.
[0008] As an optimization, the high temperature solid phase method of doping lithium and cerium is to mix tin oxide, lithium carbonate and cerium oxide by ball milling and then calcining at high temperature.
[0009] As an optimization, the in-situ growth of titanium dioxide is performed by nano-spraying technology.
[0010] As an optimization, the sintering is performed using vacuum spark plasma sintering technology.
[0011] A method for preparing a silver-based tin oxide electrical contact material comprises the following preparation steps:
[0012] (1) By weight, 50-60 parts of tin oxide, 2-3 parts of lithium carbonate, and 0.25-0.3 parts of cerium oxide were mixed evenly, added to a ball mill, and 8-10 parts of ethanol, 1-2 parts of polyvinyl pyrrolidone, and zirconium oxide balls were added. The mixture was ball-milled at a speed of 400-500 rpm for 9-10 hours at a ball-to-material ratio of 10:1, dried at 60-70°C for 5-6 hours, calcined at 1000-1100°C for 11-12 hours, and passed through a 325 mesh sieve after grinding to obtain doped tin oxide powder;
[0013] (2) Add 10-12 parts of tin chloride pentahydrate to 80-90 parts of polyvinyl pyrrolidone solution by weight, stir at 40-45°C, 150-200 r / min for 10-12 hours, add 0.3-0.4 parts of copper nitrate trihydrate, continue stirring for 60-80 minutes, put it into the spinning needle tube, the distance between the needle tip and the collecting roller is 18 cm, place a nano atomizer filled with 40-50 parts of butyl titanate ethanol solution on the collecting roller, the spray direction is orthogonal to the collecting roller, the distance between the nano atomizer and the collecting roller is 18 cm, and perform electrostatic spinning at a voltage of 18-20 KV, a spinning propulsion speed of 1 ml / h, room temperature, and 40%-50% RH. After collecting from the collecting roller, put it into a vacuum oven at 70-80°C for vacuum drying for 10-12 hours, heat-treat in an air atmosphere, and naturally cool to room temperature to obtain doped tin oxide fiber;
[0014] (3) Add 10-12 parts of doped tin oxide powder and 83-85 parts of silver powder into a ball mill, then add 13.5-14.5 parts of anhydrous ethanol and zirconium oxide balls, and mill at a ball-to-material ratio of 10:1 at a speed of 600-700 rpm for 50-60 min. Then add 3-5 parts of doped tin oxide fiber, mill at a speed of 250-350 rpm for 15-20 min, vacuum dry at 50-60°C for 4-5 h, anneal in a muffle furnace at 500°C for 100-120 min, and pass through a 325 mesh sieve after grinding to obtain a silver-based tin oxide composite powder.
[0015] (4) The silver-based tin oxide composite powder is placed in a graphite mold for pre-pressing, an external pressure of 120 MPa is applied, the pressure is maintained for 2 minutes, and the powder is placed in a vacuum discharge plasma furnace for sintering. The sintering pressure is 45-50 MPa. The sintering system is to increase the temperature to 500-600°C at a heating rate of 60°C / min, and then increase the temperature to 800-900°C at a heating rate of 40°C / min and sinter for 10 minutes. The powder is naturally cooled to room temperature. After demolding, the powder is kept at 600°C for 2 hours in an air atmosphere for decarbonization to obtain a silver-based tin oxide electrical contact material.
[0016] As an optimization, the polyvinyl pyrrolidone model in step (1) is K30.
[0017] As an optimization, the mass fraction of polyvinyl pyrrolidone in the polyvinyl pyrrolidone solution in step (2) is 15%, the solvent is a mixed solvent of ethanol and N,N-dimethylformamide, the mass ratio of ethanol to N,N-dimethylformamide is 1:1, and the model of polyvinyl pyrrolidone is K30.
[0018] As an optimization, the concentration of the butyl titanate ethanol solution in step (2) is 0.02 mol / L.
[0019] As an optimization, the heat treatment in step (2) is firstly to heat the mixture to 240-260°C at a heating rate of 2°C / min and calcine for 1 hour, then to heat the mixture to 440-460°C at a heating rate of 0.6-0.8°C / min and calcine for 1 hour, and finally to heat the mixture to 600-620°C at a heating rate of 0.8-0.9°C / min and calcine for 3-4 hours.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] When preparing the silver-based tin oxide electric contact material, the present invention firstly adopts a high-temperature solid phase method to dope lithium and cerium to prepare doped tin oxide powder; tin chloride and copper nitrate are electrostatically spun to form a fiber membrane, and titanium dioxide is in situ grown by nano-spraying, and then calcined to form doped tin oxide fiber; doped tin oxide powder, doped tin oxide fiber and silver powder are mixed by high-energy ball milling and then annealed to obtain silver-based tin oxide composite powder; the silver-based tin oxide composite powder is pre-pressed and then vacuum discharge plasma sintering is performed to obtain the silver-based tin oxide electric contact material.
[0022] Firstly, lithium and cerium are doped by a high-temperature solid phase method to prepare doped tin oxide powder. Tin oxide, lithium carbonate and cerium oxide are wet-milled in a ball mill and then calcined at a high temperature to prepare doped tin oxide powder. The doped tin oxide powder is subsequently added to a silver matrix as a reinforcing phase. Due to the poor wettability of tin oxide and silver, the dispersion of tin oxide in silver is poor, which reduces the various properties of the silver-based tin oxide electrical contact material. The doping of lithium element improves this well. Lithium element has a low electronegativity and can effectively improve the wettability between tin oxide and the silver matrix, reduce the surface enrichment of tin oxide, reduce mass loss, improve the stability of contact resistance, and extend the electrical life. As a rare metal, cerium has a trace amount of After doping, the grains can be effectively refined and impurities in the raw materials can be purified. At the same time, rare earth elements will generate compounds with high melting points and light specific gravity with these impurities. At the same time, during the fusion welding process, these high-melting point compounds will float up to form slag and suspend on the surface of molten silver to prevent splashing and loss of silver liquid, and improve the resistance to fusion welding and corrosion. The co-doping of lithium and cerium elements enables them to play a better effect. The improvement of lithium on wettability and the role of cerium in refining grains and purifying impurities can more effectively improve the resistance to fusion welding and arc erosion of electrical contact materials, and increase electrical life. At the same time, a small amount of cerium doping can also improve the brittleness of the material and improve its processing performance and plasticity.
[0023] Secondly, tin chloride and copper nitrate are made into fiber membranes by electrospinning, and titanium dioxide is grown in situ by nano-spraying. After calcination, doped tin oxide fibers are made. Nano-scale fiber filaments are formed by electrospinning. The calcination system and process conditions during the heat treatment process are controlled to form a good fiber filament morphology. Tin and copper elements are added to the spinning solution at the same time. Copper-doped tin oxide fiber filaments can be formed during the calcination process. In the spinning process, butyl titanate is sprayed on the fiber membrane formed by spinning by nano-spraying technology. Butyl titanate can react with water vapor in the air to generate titanium dioxide in situ, thereby uniformly loading titanium dioxide on the fiber membrane formed by spinning. Subsequently, during the heat treatment process, the lattice of tin oxide is diffused into the tin oxide by high-temperature diffusion, thereby improving the band gap width of tin oxide and improving its conductive properties. At the same time, the co-doping of copper and titanium improves the wettability of the fiber, improves its bonding force with the silver matrix, effectively improves the mechanical strength of the electrical contact material, and improves its processing performance. At the same time, the fibrous tin oxide has good arc erosion resistance, is not easy to decompose after multiple arc ablation, and reduces the mass loss of the contact.
[0024] Finally, the doped tin oxide powder, doped tin oxide fiber and silver powder are mixed by high-energy ball milling and then annealed to obtain a silver-based tin oxide composite powder; the silver-based tin oxide composite powder is pre-pressed and then vacuum discharge plasma sintered to obtain a silver-based tin oxide electrical contact material. The three materials are mixed by high-energy ball milling, and then annealing is performed to remove the internal stress caused by ball milling. Then, the mixed silver-based tin oxide composite powder is sintered using vacuum discharge plasma sintering technology. The products prepared by conventional powder metallurgy have limited density, low material density, large oxide particles, uneven distribution, and poor overall performance. Discharge plasma sintering is to apply a large current to the material itself under a vacuum and low voltage environment to produce a spark discharge effect in the material molecules, thereby It is transformed into a plasma state, in which high-energy pulses are formed between molecules, thereby bonding the molecules together. In this process, pressure is applied at the same time to reduce the distance between molecules and improve the overall density. At the same time, vacuum discharge plasma sintering will still cause cracks and pores when sintering materials with poor wettability, thereby reducing the material performance. Therefore, the aforementioned doping modification of tin oxide powder and the addition of doped tin oxide fibers have effectively improved the poor wettability, so that the vacuum discharge plasma sintering technology can be better used to obtain silver-based tin oxide electrical contact materials with excellent performance. At the same time, the vacuum discharge plasma sintering process is simple, and does not require repeated pressing and firing like traditional powder metallurgy processes, and can be sintered and formed in one time. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Embodiment 1:
[0026] A method for preparing a silver-based tin oxide electrical contact material, the method comprising the following steps:
[0027] (1) By weight, 50 parts of tin oxide, 2 parts of lithium carbonate, and 0.25 parts of cerium oxide were mixed evenly, added to a ball mill, and 8 parts of ethanol, 1 part of polyvinyl pyrrolidone, and zirconium oxide balls were added. The mixture was ball-milled at a speed of 400 rpm for 10 h at a ball-to-material ratio of 10:1, dried at 60°C for 6 h, calcined at 1000°C for 12 h, and passed through a 325 mesh sieve after grinding to obtain doped tin oxide powder;
[0028] (2) By mass, add 10 parts of tin chloride pentahydrate to 80 parts of polyvinyl pyrrolidone solution, stir at 40°C, 150 r / min for 12 h, add 0.3 parts of copper nitrate trihydrate, continue stirring for 60 min, put into the spinning needle tube, the distance between the needle tip and the collecting drum is 18 cm, place the nano atomizer filled with 40 parts of 0.02 mol / L butyl titanate ethanol solution on the collecting drum, the spray direction is orthogonal to the collecting drum, and the distance between the nano atomizer and the collecting drum is 18 cm. Electrospinning was performed at a voltage of 18KV, a spinning speed of 1ml / h, room temperature, and 40%RH. After being collected from the collecting drum, the fibers were placed in a vacuum oven and dried at 70°C for 12h. In an air atmosphere, the fibers were first heated to 240°C at a heating rate of 2°C / min and calcined for 1h. Then, the fibers were heated to 440°C at a heating rate of 0.6°C / min and calcined for 1h. Finally, the fibers were heated to 600°C at a heating rate of 0.8°C / min and calcined for 4h. The fibers were naturally cooled to room temperature to obtain doped tin oxide fibers.
[0029] (3) Add 10 parts of doped tin oxide powder and 85 parts of silver powder into a ball mill, then add 13.5 parts of anhydrous ethanol and zirconium oxide balls, and mill for 60 min at a ball-to-material ratio of 10:1 at a speed of 600 rpm. Then add 5 parts of doped tin oxide fiber, mill for 20 min at a speed of 250 rpm, vacuum dry at 50°C for 5 h, anneal in a muffle furnace at 500°C for 100 min, and pass through a 325 mesh sieve after grinding to obtain a silver-based tin oxide composite powder;
[0030] (4) The silver-based tin oxide composite powder was placed in a graphite mold for pre-pressing, an external pressure of 120 MPa was applied, the pressure was maintained for 2 min, and the powder was placed in a vacuum discharge plasma furnace for sintering. The sintering pressure was 45 MPa. The sintering system was heated to 500 °C at a heating rate of 60 °C / min, and then heated to 800 °C at a heating rate of 40 °C / min for 10 min. The powder was naturally cooled to room temperature. After demolding, the powder was kept at 600 °C for 2 h in an air atmosphere for decarbonization to obtain a silver-based tin oxide electrical contact material. Embodiment 2:
[0031] A method for preparing a silver-based tin oxide electrical contact material, the method comprising the following steps:
[0032] (1) By weight, 55 parts of tin oxide, 2.5 parts of lithium carbonate, and 0.28 parts of cerium oxide were mixed evenly, added to a ball mill, and 9 parts of ethanol, 1.5 parts of polyvinyl pyrrolidone, and zirconium oxide balls were added. The mixture was ball-milled at a speed of 450 rpm for 9.5 h at a ball-to-material ratio of 10:1, dried at 65°C for 5.5 h, calcined at 1050°C for 11.5 h, and passed through a 325 mesh sieve after grinding to obtain doped tin oxide powder;
[0033] (2) By weight, 11 parts of tin chloride pentahydrate were added to 85 parts of polyvinyl pyrrolidone solution, stirred at 42°C and 175 r / min for 11 h, 0.35 parts of copper nitrate trihydrate were added, and stirring was continued for 70 min. The solution was loaded into a spinning needle tube, with the distance between the needle tip and the collecting drum being 18 cm. A nano atomizer containing 45 parts of 0.02 mol / L butyl titanate ethanol solution was placed on the collecting drum, with the spray direction orthogonal to the collecting drum and the distance between the nano atomizer and the collecting drum being 18 cm. The voltage was 19KV, the spinning speed was 1ml / h, the room temperature and 45%RH were used for electrospinning, and the fibers were collected from the collecting drum and placed in a vacuum oven for vacuum drying at 75°C for 11h. In an air atmosphere, the fibers were first heated to 250°C at a heating rate of 2°C / min and calcined for 1h, then heated to 450°C at a heating rate of 0.7°C / min and calcined for 1h, and finally heated to 610°C at a heating rate of 0.85°C / min and calcined for 3.5h. The fibers were naturally cooled to room temperature to obtain doped tin oxide fibers.
[0034] (3) Add 11 parts of doped tin oxide powder and 84 parts of silver powder into a ball mill, then add 14 parts of anhydrous ethanol and zirconium oxide balls, and mill at a ball-to-material ratio of 10:1 at a speed of 650 rpm for 55 min. Then add 4 parts of doped tin oxide fiber, mill at a speed of 300 rpm for 18 min, vacuum dry at 55°C for 4.5 h, anneal in a muffle furnace at 500°C for 110 min, and pass through a 325 mesh sieve after grinding to obtain a silver-based tin oxide composite powder.
[0035] (4) The silver-based tin oxide composite powder was placed in a graphite mold for pre-pressing, an external pressure of 120 MPa was applied, the pressure was maintained for 2 min, and the powder was placed in a vacuum discharge plasma furnace for sintering. The sintering pressure was 48 MPa. The sintering system was heated to 550°C at a heating rate of 60°C / min, and then heated to 850°C at a heating rate of 40°C / min and sintered for 10 min. The powder was naturally cooled to room temperature. After demolding, the powder was kept at 600°C for 2 h in an air atmosphere for decarbonization to obtain a silver-based tin oxide electrical contact material. Embodiment 3:
[0036] A method for preparing a silver-based tin oxide electrical contact material, the method comprising the following steps:
[0037] (1) By weight, 60 parts of tin oxide, 3 parts of lithium carbonate, and 0.3 parts of cerium oxide were mixed evenly, added to a ball mill, and 10 parts of ethanol, 2 parts of polyvinyl pyrrolidone, and zirconium oxide balls were added. The mixture was ball-milled at a speed of 500 rpm for 9 hours at a ball-to-material ratio of 10:1, dried at 70°C for 5 hours, calcined at 1100°C for 11 hours, and passed through a 325 mesh sieve after grinding to obtain doped tin oxide powder;
[0038] (2) By mass, 12 parts of tin chloride pentahydrate were added to 90 parts of polyvinyl pyrrolidone solution, stirred at 45°C and 200 r / min for 10 h, 0.4 parts of copper nitrate trihydrate were added, and stirring was continued for 80 min. The spinning needle tube was loaded, and the distance between the needle tip and the collecting drum was 18 cm. A nano atomizer filled with 50 parts of 0.02 mol / L butyl titanate ethanol solution was placed on the collecting drum, and the spray direction was orthogonal to the collecting drum. The distance between the nano atomizer and the collecting drum was 18 cm. Electrospinning was performed at a voltage of 20 KV, a spinning speed of 1 ml / h, room temperature, and 50% RH. After being collected from the collecting drum, the fibers were placed in a vacuum oven and dried at 80°C for 10 h. In an air atmosphere, the fibers were first heated to 260°C at a heating rate of 2°C / min and calcined for 1 h. Then, the fibers were heated to 460°C at a heating rate of 0.8°C / min and calcined for 1 h. Finally, the fibers were heated to 620°C at a heating rate of 0.9°C / min and calcined for 3 h. The fibers were naturally cooled to room temperature to obtain doped tin oxide fibers.
[0039] (3) Add 12 parts of doped tin oxide powder and 83 parts of silver powder into a ball mill, then add 14.5 parts of anhydrous ethanol and zirconium oxide balls, and mill for 50 min at a ball-to-material ratio of 10:1 at a speed of 700 rpm. Then add 3 parts of doped tin oxide fiber, mill for 15 min at a speed of 350 rpm, vacuum dry at 60°C for 4 h, anneal in a muffle furnace at 500°C for 120 min, and pass through a 325 mesh sieve after grinding to obtain a silver-based tin oxide composite powder;
[0040] (4) The silver-based tin oxide composite powder was placed in a graphite mold for pre-pressing, an external pressure of 120 MPa was applied, the pressure was maintained for 2 min, and the powder was placed in a vacuum discharge plasma furnace for sintering. The sintering pressure was 50 MPa. The sintering system was to increase the temperature to 600 °C at a heating rate of 60 °C / min, and then increase the temperature to 900 °C at a heating rate of 40 °C / min and sinter for 10 min. The powder was naturally cooled to room temperature. After demolding, the powder was kept at 600 °C for 2 h in an air atmosphere for decarbonization to obtain a silver-based tin oxide electrical contact material.
[0041] Comparative Example 1:
[0042] The preparation method of the silver-based tin oxide electrical contact material of Comparative Example 1 is different from that of Example 2 in that step (2) is different. Step (2) is modified as follows: by weight, 11 parts of tin chloride pentahydrate are added to 85 parts of polyvinyl pyrrolidone solution, stirred at 42°C and 175 r / min for 11 hours, 0.35 parts of copper nitrate trihydrate are added, and stirring is continued for 70 minutes. The spinning needle tube is loaded, and the distance between the needle tip and the collecting roller is 18 cm. The spinning pusher is operated at a voltage of 19 kV. The feed rate was 1 ml / h, room temperature, 45% RH, electrospinning was performed, and after being collected from the collection drum, it was placed in a vacuum oven and vacuum dried at 75°C for 11 hours, and in an air atmosphere, the temperature was first increased to 250°C at a heating rate of 2°C / min and calcined for 1 hour, then increased to 450°C at a heating rate of 0.7°C / min and calcined for 1 hour, and finally increased to 610°C at a heating rate of 0.85°C / min and calcined for 3.5 hours, and naturally cooled to room temperature to obtain doped tin oxide fibers. The remaining steps are the same as in Example 2.
[0043] Comparative Example 2:
[0044] The preparation method of the silver-based tin oxide electrical contact material of Comparative Example 2 is different from that of Example 2 in that step (2) is different. Step (2) is modified as follows: by mass, 11 parts of tin chloride pentahydrate are added to 85 parts of polyvinyl pyrrolidone solution, stirred at 42°C and 175 r / min for 11 h, and loaded into a spinning needle tube, with the distance between the needle tip and the collecting roller being 18 cm, and a nano-atomizer filled with 45 parts of 0.02 mol / L butyl titanate ethanol solution is placed at the collecting roller, with the spray direction being orthogonal to the collecting roller, and the nano-atomizer and the collecting roller being at an angle of 1.004 mm. The distance between the cylinders was 18 cm, and the voltage was 19 KV, the spinning speed was 1 ml / h, the room temperature, and 45% RH, and electrospinning was performed. After being collected from the collecting drum, it was placed in a vacuum oven and vacuum dried at 75°C for 11 hours. In an air atmosphere, the temperature was first increased to 250°C at a heating rate of 2°C / min and calcined for 1 hour, then increased to 450°C at a heating rate of 0.7°C / min and calcined for 1 hour, and finally increased to 610°C at a heating rate of 0.85°C / min and calcined for 3.5 hours, and naturally cooled to room temperature to obtain doped tin oxide fibers. The remaining steps are the same as in Example 2.
[0045] Comparative Example 3:
[0046] The preparation method of the silver-based tin oxide electrical contact material of Comparative Example 3 differs from that of Example 2 in that step (2) is different. Step (2) is modified as follows: 11 parts of tin chloride pentahydrate are added to 85 parts of polyvinyl pyrrolidone solution by mass, stirred at 42°C and 175 r / min for 11 h, loaded into a spinning needle tube, with the distance between the needle tip and the collecting roller being 18 cm, and electrospinning is performed at a voltage of 19 KV, a spinning propulsion speed of 1 ml / h, room temperature, and 45% RH. After being collected from the collecting roller, the solution is placed in a vacuum oven and vacuum dried at 75°C for 11 h. In an air atmosphere, the solution is first heated to 250°C at a heating rate of 2°C / min and calcined for 1 h, then heated to 450°C at a heating rate of 0.7°C / min and calcined for 1 h, and finally heated to 610°C at a heating rate of 0.85°C / min and calcined for 3.5 h. The solution is naturally cooled to room temperature to obtain tin oxide fiber. Step (3) is modified as follows: 11 parts of doped tin oxide powder and 84 parts of silver powder are added to a ball mill, and then 14 parts of anhydrous ethanol and zirconium oxide balls are added. The mixture is milled at a speed of 650 rpm for 55 min at a ball-to-material ratio of 10:1. Then 4 parts of tin oxide fibers are added. The mixture is milled at a speed of 300 rpm for 18 min. The mixture is vacuum dried at 55° C. for 4.5 h, annealed at 500° C. for 110 min in a muffle furnace, and passed through a 325-mesh sieve after grinding to obtain a silver-based tin oxide composite powder. The remaining steps are the same as those in Example 2.
[0047] Comparative Example 4:
[0048] The preparation method of the silver-based tin oxide electrical contact material of Comparative Example 4 is different from that of Example 2 in that step (2) is not performed, and step (3) is modified as follows: 15 parts of doped tin oxide powder and 84 parts of silver powder are added to a ball mill, and then 14 parts of anhydrous ethanol and zirconium oxide balls are added. The ball-to-material ratio is 10:1, the rotation speed is 650 rpm, and the ball milling is performed for 55 minutes. The ball milling is performed under vacuum at 55° C. for 4.5 hours, and the ball milling is performed in a muffle furnace at 500° C. for 110 minutes. The ball milling is performed through a 325-mesh sieve after grinding to obtain a silver-based tin oxide composite powder. The remaining steps are the same as those of Example 2.
[0049] Comparative Example 5:
[0050] The preparation method of the silver-based tin oxide electrical contact material of Comparative Example 5 is different from that of Example 2 in step (1), and step (1) is modified as follows: 55 parts of tin oxide and 2.5 parts of lithium carbonate are mixed uniformly by mass, added to a ball mill, 9 parts of ethanol, 1.5 parts of polyvinyl pyrrolidone, and zirconium oxide balls are added, and the ball-to-material ratio is 10:1, the rotation speed is 450 rpm, and the ball milling is carried out for 9.5 hours, and the ball milling is carried out for 5.5 hours at 65° C., and the ball milling is carried out for 11.5 hours at 1050° C. After grinding, the powder is passed through a 325 mesh sieve to obtain a doped tin oxide powder. The remaining steps are the same as those of Example 2.
[0051] Comparative Example 6:
[0052] The preparation method of the silver-based tin oxide electrical contact material of Comparative Example 6 is different from that of Example 2 in step (1), and step (1) is modified as follows: 55 parts of tin oxide and 0.28 parts of cerium oxide are mixed uniformly by mass, added to a ball mill, 9 parts of ethanol, 1.5 parts of polyvinyl pyrrolidone, and zirconium oxide balls are added, and the ball-to-material ratio is 10:1, the rotation speed is 450 rpm, and the ball milling is carried out for 9.5 hours, and the ball milling is carried out for 5.5 hours at 65°C, and the ball milling is carried out for 11.5 hours at 1050°C. After grinding, the powder is passed through a 325 mesh sieve to obtain a doped tin oxide powder. The remaining steps are the same as those of Example 2.
[0053] Comparative Example 7:
[0054] The preparation method of the silver-based tin oxide electrical contact material of Comparative Example 7 is different from that of Example 2 in that step (1) is not performed, and step (3) is modified as follows: by weight, 11 parts of tin oxide and 84 parts of silver powder are added to a ball mill, and then 14 parts of anhydrous ethanol and zirconium oxide balls are added. The ball-to-material ratio is 10:1, and the rotation speed is 650 rpm for 55 minutes. Then, 4 parts of doped tin oxide fibers are added, the rotation speed is 300 rpm, and the ball milling is performed for 18 minutes. The mixture is vacuum dried at 55° C. for 4.5 hours, annealed at 500° C. for 110 minutes in a muffle furnace, and passed through a 325 mesh sieve after grinding to obtain a silver-based tin oxide composite powder. The remaining steps are the same as those of Example 2.
[0055] Comparative Example 8:
[0056] The preparation method of the silver-based tin oxide electrical contact material of Comparative Example 8 is different from that of Example 2 in that step (4) is different. Step (4) is modified as follows: the silver-based tin oxide composite powder is placed in a mold for pre-pressing, an external pressure of 120 MPa is applied, the pressure is maintained for 40 seconds, the temperature is increased to 100°C at a heating rate of 2°C / min and maintained for 1 hour, the temperature is then increased to 420°C at a heating rate of 3°C / min and maintained for 1 hour, the temperature is further increased to 750°C at a heating rate of 3°C / min and maintained for 1 hour, and finally the temperature is increased to 920°C at a heating rate of 1°C / min and maintained for 3 hours, and the temperature is naturally cooled to 300°C, and the temperature is re-pressed at 300°C at a pressure of 1200 MPa for 40 seconds, and then the temperature is increased to 860°C at a heating rate of 4°C / min and re-fired for 2 hours, and the temperature is naturally cooled to room temperature to obtain the silver-based tin oxide electrical contact material. The remaining steps are the same as those of Example 2.
[0057] The silver-based tin oxide electrical contact materials prepared in the above-mentioned embodiments and comparative examples were made into corresponding samples by drawing, hot extrusion and other processes according to the relevant requirements of the following test examples.
[0058] Test Example 1:
[0059] Mechanical property test: The tensile strength, elongation after fracture, Vickers hardness and density of the prepared silver-based tin oxide electrical contact material were tested to evaluate its mechanical strength performance. The silver-based tin oxide electrical contact material was made into a wire sample with a diameter of 3.4 mm. The specific test method is as follows:
[0060] Tensile strength and elongation after fracture: refer to the standard JB / T 7780.4-2008 to test the tensile strength and elongation of the sample at room temperature. Test 5 samples in each group and take the average value for record.
[0061] Vickers hardness: Refer to the standard JB / T 7780.2-2008 to test the Vickers hardness of the sample. Test 5 samples in each group and take the average value for record.
[0062] Density: Refer to standard JB / T 7780.1-2008 and use the drainage method to test the density of the sample. Test 5 samples in each group and take the average value for record.
[0063] The results are shown in Table 1.
[0064] Table 1
[0065] Tensile strength / MPa Elongation after fracture Vickers hardness / HV <![CDATA[Density / g·cm -3 > Example 1 301.4 24.13% 107.42 9.804 Example 2 303.8 24.54% 108.31 9.816 Example 3 303.2 23.88% 107.28 9.798 Comparative Example 1 294.3 22.54% 105.14 9.787 Comparative Example 2 271.4 20.15% 104.28 9.641 Comparative Example 3 262.5 18.44% 103.83 9.612 Comparative Example 4 245.1 22.32% 102.46 9.788 Comparative Example 5 284.7 16.64% 103.54 9.761 Comparative Example 6 281.5 19.37% 101.28 9.524 Comparative Example 7 263.6 11.29% 94.37 9.431 Comparative Example 8 264.9 20.48% 87.22 9.037
[0066] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 8 in Table 1, it can be found that the silver-based tin oxide electrical contact material prepared by the present invention has good mechanical strength.
[0067] By comparing the data in the table, it is shown that the addition of doped tin oxide fiber and its doping modification effectively improve the tensile strength, the co-doping of copper and titanium improves the wettability of tin oxide fiber, enhances its bonding with the silver matrix, and improves the reduction of elongation after fracture caused by the addition of fiber, thereby improving the tensile strength while ensuring the processing performance; the co-doping of lithium and cerium with the reinforcing phase tin oxide also effectively improves the tensile strength, elongation after fracture and Vickers hardness, the doping of lithium element improves the wettability of tin oxide and the silver matrix, and the cerium element purifies impurities and refines the grains, and the two work together to improve the mechanical properties of the electrical contact material; the application of vacuum discharge plasma sintering technology has a significant improvement on each performance, and at the same time improves the density, and the improvement of the wettability of tin oxide fiber and tin oxide powder combined with the application of vacuum discharge plasma sintering technology effectively improves the density.
[0068] Test Example 2:
[0069] Resistivity test: refer to the standard JB / T 7780.3-2008 to test the resistivity of the sample. The sample uses the wire sample used in Test Example 1. The resistance of the sample is tested using a DC digital resistance tester. The resistivity calculation formula in the standard is used to calculate the resistivity of the sample in μΩ·cm. Five samples are tested in each group and the average value is recorded.
[0070] The results are shown in Table 2.
[0071] Table 2
[0072] Resistivity / μΩ·cm Resistivity / μΩ·cm Example 1 2.185 Comparative Example 1 2.424 Example 2 2.173 Comparative Example 2 2.485 Example 3 2.177 Comparative Example 3 2.621 Comparative Example 4 2.214 Comparative Example 5 2.431 Comparative Example 6 2.488 Comparative Example 7 2.897 Comparative Example 8 2.554
[0073] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 8 in Table 2, it can be found that the silver-based tin oxide electrical contact material prepared by the present invention has a lower resistivity and good conductive performance.
[0074] By comparing the data in the table, it is shown that the addition of doped tin oxide fiber and its doping modification effectively improve the resistivity, and the co-doping of copper and titanium improves the wettability of tin oxide fiber, thereby enhancing its bonding strength with the silver matrix, improving the density, and reducing the generation of cracks and pores; the co-doping of lithium and cerium with the reinforcing phase tin oxide also effectively improves the resistivity. The doping of lithium improves the wettability of tin oxide and the silver matrix, and the cerium purifies impurities and refines the grains. The two work together to improve the resistivity of the electrical contact material; the application of vacuum discharge plasma sintering technology improves the overall crystal structure of the material, thereby improving the density and resistivity at the same time.
[0075] Test Example 3:
[0076] Test of anti-melting welding and anti-arc erosion performance: The wire prepared in Test Example 1 is made into a rivet-type contact sample with a top diameter of 3mm, a thickness of 0.6mm, a bottom diameter of 1.4mm, and a contact length of 1.5mm. The prepared rivet-type contact sample is subjected to a dot test 30,000 times using a JF04C model electrical contact material testing machine. The parameters are set as voltage 18V, current 15A, 30,000 on-off times, contact pressure 80cN, test time interval 450ms, and contact opening distance 1mm. After completing the dot test, the average value of the last thousand tests is recorded. The fusion welding force is the magnitude of the force required to separate the two contacts when the contacts are welded. The anti-melting welding performance of the sample is evaluated by the magnitude of the fusion welding force; after completing the dot test, the roughness and mass loss of the contact surface are tested. The arc erosion resistance of the prepared silver-based tin oxide electrical contact material is evaluated by the magnitude of the surface roughness and mass loss. Five samples are tested in each group, and the average value is recorded.
[0077] The results are shown in Table 3.
[0078] Table 3
[0079] Welding force Quality loss Roughness Example 1 3.14cN 0.0189g 0.224μm Example 2 2.97cN 0.0176g 0.215μm Example 3 3.02cN 0.0185g 0.217μm Comparative Example 1 6.18cN 0.0274g 0.292μm Comparative Example 2 8.24cN 0.0299g 0.316μm Comparative Example 3 13.57cN 0.0356g 0.374μm Comparative Example 4 31.44cN 0.0614g 0.622μm Comparative Example 5 11.26cN 0.0322g 0.355μm Comparative Example 6 15.47cN 0.0384g 0.419μm Comparative Example 7 28.44cN 0.0577g 0.589μm Comparative Example 8 12.25cN 0.0341g 0.397μm
[0080] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 8 in Table 3, it can be found that the silver-based tin oxide electrical contact material prepared by the present invention has good resistance to fusion welding and arc erosion.
[0081] The comparison of the data in the table shows that the addition of doped tin oxide fiber and its doping modification effectively improve the resistance to fusion welding and arc erosion. The co-doping of copper and titanium improves the wettability of tin oxide fiber, and enhances its bonding strength with the silver matrix. The fibrous tin oxide has good resistance to arc erosion and fusion welding, and can inhibit the splashing of molten silver. The co-doping of lithium and cerium with the reinforcing phase tin oxide also effectively improves the resistance to fusion welding and arc erosion. The doping of lithium improves the wettability of tin oxide with the silver matrix, and the cerium The elements purify impurities and refine grains. The combined effect of the two improves the resistance of electrical contact materials to fusion welding and arc erosion. Cerium will react with these impurities to form compounds with high melting point and light specific gravity. At the same time, during the fusion welding process, these high-melting point compounds will float up to form slag and suspend on the surface of molten silver, preventing splashing and loss of silver liquid, thereby improving resistance to fusion welding and arc erosion. The application of vacuum discharge plasma sintering technology improves the overall crystal structure of the material, increasing the density while improving resistance to fusion welding and arc erosion.
[0082] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A silver-based tin oxide electrical contact material, characterized in that: The silver-based tin oxide electrical contact material is prepared by firstly doping lithium and cerium by a high-temperature solid phase method to prepare doped tin oxide powder; electrostatically spinning tin chloride and copper nitrate to form a fiber membrane while in-situ growing titanium dioxide, and calcining to prepare doped tin oxide fiber; mixing doped tin oxide powder, doped tin oxide fiber and silver powder by high-energy ball milling and then annealing to prepare silver-based tin oxide composite powder; pre-pressing the silver-based tin oxide composite powder and then sintering to prepare the silver-based tin oxide electrical contact material; The sintering is performed using vacuum spark plasma sintering technology.
2. The silver-based tin oxide electrical contact material according to claim 1, characterized in that: The high temperature solid phase method of doping lithium and cerium is to mix tin oxide, lithium carbonate and cerium oxide by ball milling and then calcine at high temperature.
3. The silver-based tin oxide electrical contact material according to claim 1, characterized in that: The in-situ growth of titanium dioxide is carried out by nano-spraying technology.
4. A method for preparing a silver-based tin oxide electrical contact material, characterized in that: The method comprises the following preparation steps: (1) By weight, 50-60 parts of tin oxide, 2-3 parts of lithium carbonate, and 0.25-0.3 parts of cerium oxide were mixed evenly, added to a ball mill, and 8-10 parts of ethanol, 1-2 parts of polyvinyl pyrrolidone, and zirconium oxide balls were added. The mixture was ball-milled at a speed of 400-500 rpm for 9-10 hours at a ball-to-material ratio of 10:1, dried at 60-70°C for 5-6 hours, calcined at 1000-1100°C for 11-12 hours, and passed through a 325 mesh sieve after grinding to obtain doped tin oxide powder; (2) Add 10-12 parts of tin chloride pentahydrate to 80-90 parts of polyvinyl pyrrolidone solution by weight, stir at 40-45°C, 150-200 r / min for 10-12 hours, add 0.3-0.4 parts of copper nitrate trihydrate, continue stirring for 60-80 minutes, put it into the spinning needle tube, the distance between the needle tip and the collecting roller is 18 cm, place a nano atomizer filled with 40-50 parts of butyl titanate ethanol solution on the collecting roller, the spray direction is orthogonal to the collecting roller, the distance between the nano atomizer and the collecting roller is 18 cm, and perform electrostatic spinning at a voltage of 18-20 KV, a spinning propulsion speed of 1 ml / h, room temperature, and 40%-50% RH. After collecting from the collecting roller, put it into a vacuum oven at 70-80°C for vacuum drying for 10-12 hours, heat-treat in an air atmosphere, and naturally cool to room temperature to obtain doped tin oxide fiber; (3) Add 10-12 parts of doped tin oxide powder and 83-85 parts of silver powder into a ball mill, then add 13.5-14.5 parts of anhydrous ethanol and zirconium oxide balls, and mill at a ball-to-material ratio of 10:1 at a speed of 600-700 rpm for 50-60 min. Then add 3-5 parts of doped tin oxide fiber, mill at a speed of 250-350 rpm for 15-20 min, vacuum dry at 50-60°C for 4-5 h, anneal in a muffle furnace at 500°C for 100-120 min, and pass through a 325 mesh sieve after grinding to obtain a silver-based tin oxide composite powder. (4) The silver-based tin oxide composite powder is placed in a graphite mold for pre-pressing, an external pressure of 120 MPa is applied, the pressure is maintained for 2 minutes, and the powder is placed in a vacuum discharge plasma furnace for sintering. The sintering pressure is 45-50 MPa. The sintering system is to increase the temperature to 500-600°C at a heating rate of 60°C / min, and then increase the temperature to 800-900°C at a heating rate of 40°C / min and sinter for 10 minutes. The powder is naturally cooled to room temperature. After demolding, the powder is kept at 600°C for 2 hours in an air atmosphere for decarbonization to obtain a silver-based tin oxide electrical contact material.
5. The method for preparing a silver-based tin oxide electrical contact material according to claim 4, characterized in that: The polyvinyl pyrrolidone model in step (1) is K30.
6. The method for preparing a silver-based tin oxide electrical contact material according to claim 4, characterized in that: The mass fraction of polyvinyl pyrrolidone in the polyvinyl pyrrolidone solution in step (2) is 15%, the solvent is a mixed solvent of ethanol and N,N-dimethylformamide, the mass ratio of ethanol to N,N-dimethylformamide is 1:1, and the model of polyvinyl pyrrolidone is K30.
7. The method for preparing a silver-based tin oxide electrical contact material according to claim 4, characterized in that: The concentration of the butyl titanate ethanol solution in step (2) is 0.02 mol / L.
8. The method for preparing a silver-based tin oxide electrical contact material according to claim 4, characterized in that: The heat treatment in step (2) is to first heat the temperature to 240-260°C at a heating rate of 2°C / min and calcine for 1 hour, then heat the temperature to 440-460°C at a heating rate of 0.6-0.8°C / min and calcine for 1 hour, and finally heat the temperature to 600-620°C at a heating rate of 0.8-0.9°C / min and calcine for 3-4 hours.
Citation Information
Patent Citations
Preparation method of fiber particle blending reinforced silver tin oxide electrical contact alloy
CN111663086A
Method for preparing silver tin oxide electric contact material by electrostatic spinning process
CN112609247A